O ensino de história na perspectiva da emancipação humana: contribuições para pensar a escola pública contemporânea - Batista, Elisângela (2020)
This study discusses the history teaching from the human emancipation perspective. It can be observed, through the current educational reforms and proposals, that the teaching of History, based on historical-dialectical materialism, is not essential for the State ideologically concatenated with neoliberalism. Thus, in the last instance, in the contemporary public school, work-oriented education, which denies access to all knowledge, that is, to the cultural and scientific heritage of humanity, prevails. Thus, it is necessary to understand, in the Brazil history education context, the identification of how the history teaching was inserted in this social organization process of capitalism, which paths have taken and what should be its true purpose. Therefore, the possibility of teaching history from the Historical-Critical Pedagogy (PHC) perspective is considered, in the sense of an emancipatory education, capable of breaking with the logic of capital, in which the school is inserted. Therefore, PHC is understood not only as a theory, but also as a movement that expresses itself in the perspective of change, so that the working class appropriates the scientific knowledge, heritage of humanity, produced by men, to overcome a bourgeois education.